Business Model Canvas Toko Thrifting Outdoor Impor Perspektif Ekonomi Syariah - Izzah, Raden; Eka Wahyuni, Eka Sri; Cahyono, Andi (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2025)
Data from Radar Bengkulu shows that imported outdoor thrifting in Bengkulu City reflects the trend of sustainable consumption which is increasingly in demand, especially among students and the general public. However, this practice raises concerns about its alignment with Islamic economic principles. This study aims to analyze the business model of imported outdoor thrifting stores in Bengkulu using the Business Model Canvas (BMC) approach and evaluate its compliance with Islamic economics based on Maqashid Shariah, namely justice (ʿadl), public benefit (maslahah), and transparency (ṣidq). A descriptive qualitative method with a case study approach was employed, involving five purposively selected stores. The findings show that these stores share similar business patterns across the nine BMC elements, especially in offering affordable branded products and using social media as the main distribution channel. However, not all business practices fully align with the principles of Maqashid Shariah, particularly regarding fair competition and information transparency. This research provides an initial overview of how the thrifting business can be developed ethically and sustainably by integrating Islamic values. It contributes to the discourse on Islamic economic practices in retail businesses and offers insights for entrepreneurs, regulators, and future researchers.